Intracortical Circuits in the Contralesional Primary Motor Cortex in Patients With Chronic Stroke After Botulinum Toxin Type A Injection: Case Studies - Zoghi, Maryam; Hafezi, Pouya; Amatya, Bhasker; Khan, Fary; Galea, Mary Pauline (Frontiers in Human Neuroscience, 2020)
Spasticity and motor recovery are both related to neural plasticity after stroke. A balance of activity in the primary motor cortex (M1) in both hemispheres is essential for functional recovery. In this study we assessed the intracortical inhibitory and facilitatory circuits in the contralesional M1 area in four patients with severe upper limb spasticity after chronic stroke and treated with Botulinum toxin-A (BoNT-A) injection and 12 weeks of upper limb rehabilitation. There was little to no change in the level of spasticity post-injection and only one participant experienced a small improvement in arm function. All reported improvements in quality of life. However, the levels of intracortical inhibition and facilitation in the contralesional hemisphere were different at baseline for all four participants and there was no clear pattern in the response to the intervention. Further investigation is needed to understand how BoNT-A injections affect inhibitory and facilitatory circuits in the contralesional hemisphere, the severity of spasticity, and functional improvement.